Epidemiological aspects and characterization of the resistance profile of Fusarium spp. in patients with invasive fusariosis. Issue 10 (16th August 2019) - Rosa, Priscila Dallé da; Ramirez-Castrillon, Mauricio; Borges, Rafael; Aquino, Valério; Meneghello Fuentefria, Alexandre; Zubaran Goldani, Luciano
Abstract : Introduction. The remarkable intrinsic resistance of Fusarium species to most antifungal agents results in high mortality rates in the immunocompromised population. Aims. This study aimed to investigate the epidemiology, clinical features and antifungal susceptibility of Fusarium isolates in patients with invasive fusariosis. Methodology. A total of 27 patients admitted to a referral hospital from January 2008 to June 2017 were evaluated. Antifungal susceptibility testing of isolates was performed by broth microdilution according to the Clinical and Laboratory Standards Institute guidelines. Results. Haematological malignancy was the predominant underlying condition, with an incidence of invasive fusariosis of 14.8 cases per 1000 patients with acute lymphoid leukaemia and 13.1 cases per 1000 patients with acute myeloid leukaemia. The Fusarium solani species complex (FSSC) was the most frequent agent group, followed by the Fusarium oxysporum species complex (FOSC). Voriconazole showed the best activity against Fusarium, followed by amphotericin B. Itraconazole showed high minimum inhibitory concentration values, indicating in vitro resistance. Clinical FSSC isolates were significantly ( P <0.05) more resistant to amphotericin B and voriconazole than FOSC isolates. Conclusion. The present antifungal susceptibility profiles indicate a high incidence of fusariosis in patients with haematological malignancy. Species- and strain-specific differences in antifungal susceptibility exist within Fusarium in this setting.